Steuerung von Blechmassivumformprozessen durch maßgeschneiderte tribologische Systeme - Löffler, Maria (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)
The industry is faced with a lot of requirements exemplary regarding a shortening of the process chains, a high functional integration or ecological aspects. Conventional sheet- and bulk forming operations are limited while facing such requirments. One method to meet the existing challenges is the combination of both process classes using sheet-bulk metal forming processes. Such a combination leads to a simultaneous occurance of conditions from sheet- and bulk forming operations during forming especially regarding the load conditions. These process characteristics leads to an uncontrolled material flow, in many cases yielding a reduced product quality. Within the thesis global methods to control the material flow using local adaptions of the tribological system were analyzed and evaluated regarding their effectiveness. To realizes this, the tribological mechanisms of modified tool- and workpiece surfaces were identified. These mechanisms can be used to guarantee the applicability of the results in sheet-bulk metal forming independently from the investigated parameter range within the thesi